Ipiranga: ownership and construction of an urban landscape - Tourinho, Andréa de Oliveira; Pires, Walter (Anais do Museu Paulista: História e Cultura Material, 2025)
The hill in the Ipiranga neighborhood, where the Museu Paulista and the Parque da Independência are located, maintains, since the end of the 19th century, an urban landscape of significant permanencies, even in the face of the intense transformations of the city of São Paulo in the last decades. This paper addresses the constitution process of this landscape, mainly from the perspective of land ownership, questioning the relationship between the material culture produced and the urban development. Therefore, we aim to understand the configuration and the characteristics of this territory, by investigating the interests of its owners and investors, who influenced its construction. Associated with the Independence site, this landscape nurtures for over a century the social imaginary of the Brazilian nation. However, the study presented herein seeks to analyze other processes of material and symbolic production that also provided Ipiranga with its current identity.